Laser tracking system for sports ball trajectory measurement - Ronkainen, J.; Harland, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
The sports ball market is a multi-million dollar industry; original equipment manufacturers are continually trying to develop sports balls and in order to achieve improvement in performance they often utilize launch and/or flight monitors to allow consistent measurement and benchmarking of their balls under test. This paper introduces a laser tracking system (LTS), which has been specifically designed for soccer ball tracking. This LTS combines two different concepts together in an innovative optical solution to allow the system to track an arbitrarily moving soccer ball in a completely non-contact and non-marking methodology, tracking a ball in real time up to approximately 10 m/s. The system was programmed to act as a launch monitor capable of reporting the ball launch velocity and launch angle. In order to achieve the fully functional LTS, the hardware and software choices are clearly outlined, as well as describing the tracking methodology used to achieve the real-time tracking capability.